2007
DOI: 10.1007/s00421-007-0512-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of sodium bicarbonate on surface EMG activity during repeated cycling sprints

Abstract: Abstract:The purpose of this study was to determine the effect of oral administration of sodium bicarbonate (NaHCO 3 ) on surface electromyogram (SEMG) activity from the vastus lateralis (VL) during repeated cycling sprints (RCS). Subjects performed two RCS tests (ten 10-s sprints) interspersed with both 30-s and 360-s recovery periods 1 h after oral administration of either NaHCO 3 (RCS Alk ) or CaCO 3 (RCS Pla ) in a random counterbalanced order. Recovery periods of 360 s were set before the 5th and 9th spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
14
0
4
Order By: Relevance
“…Importantly, such a reduction in agonist muscle recruitment during repeated cycle sprints has been strongly correlated (r = 0.91 to 0.98, P < 0.05, Figure 4) with the decline in mechanical output (Billaut and Smith 2009;Mendez-Villanueva et al 2008). That being said, it is interesting to note that when fatigue is moderate (e.g., fatigue index or sprint decrement score is ~10% or lower), studies have typically reported a steady level of muscle recruitment during repeated-sprint exercise (Billaut and Basset 2007;Billaut et al 2005;Girard et al 2008;Hautier et al 2000;Matsuura et al 2007). However, when the neuromuscular fatigue level is more substantial (> 20%), a concurrent decline in mechanical performance and the amplitude of EMG signals has consistently been reported across sprint repetitions (Billaut et al 2011;Mendez-Villanueva et al 2007Racinais et al 2007;Smith and Billaut 2010).…”
Section: Electromyographic Events During Repeated-sprint Exercise 41mentioning
confidence: 92%
See 1 more Smart Citation
“…Importantly, such a reduction in agonist muscle recruitment during repeated cycle sprints has been strongly correlated (r = 0.91 to 0.98, P < 0.05, Figure 4) with the decline in mechanical output (Billaut and Smith 2009;Mendez-Villanueva et al 2008). That being said, it is interesting to note that when fatigue is moderate (e.g., fatigue index or sprint decrement score is ~10% or lower), studies have typically reported a steady level of muscle recruitment during repeated-sprint exercise (Billaut and Basset 2007;Billaut et al 2005;Girard et al 2008;Hautier et al 2000;Matsuura et al 2007). However, when the neuromuscular fatigue level is more substantial (> 20%), a concurrent decline in mechanical performance and the amplitude of EMG signals has consistently been reported across sprint repetitions (Billaut et al 2011;Mendez-Villanueva et al 2007Racinais et al 2007;Smith and Billaut 2010).…”
Section: Electromyographic Events During Repeated-sprint Exercise 41mentioning
confidence: 92%
“…It is intuitive that the dramatic metabolic disturbances that occur within the exercising muscle during "all-out" and repeated sprints (for review see (Billaut and Bishop 2009)) influence the central projection of these feedbacks and thus affect the central neural drive during such intense tasks (Billaut et al 2005;MendezVillanueva et al 2008;Racinais et al 2007). That being said, the manipulation of intramuscular pH, for example, by oral administration of sodium bicarbonate does not influence EMG activity and mechanical performance during repeated cycling sprints (Matsuura et al 2007). Further studies manipulating the metabolic "milieu interieur" during sprint repetitions to examine the effects on centrally-regulated muscle recruitment are needed.…”
Section: At Least Two Potential Causes For Down-regulation Of Muscle mentioning
confidence: 99%
“…Reduced intramuscular pH by sodium bicarbonate ingestion, which in turn decreases group III/IV muscle performance during repeated 10-s cycling sprints performance during repeated 10-s cycling sprints 22) . The data reported here appear to support viewpoint 2.…”
Section: Viewpoint 2: Group Iii/iv Muscle Afferent Feedback From Actimentioning
confidence: 99%
“…However, some authors have argued that muscle fatigue results from a protective mechanism rather than the disability. They (5,7,9,18,19) have suggested that the central nervous system (CNS) modifies efferent signals to skeletal muscle and peripheral organs based on afferent signals from the skeletal muscle and peripheral organs to the CNS to prevent the failure of homeostasis and that the modification is influenced by information involving subsequent exercise. Recently, it has been reported that performance and surface electromyogram (SEMG) activity varied between conditions despite no difference in metabolic state in peripheral skeletal muscle when repeated cycling sprints were performed under light load and heavy load conditions, suggesting that efferent signals from the CNS during repeated cycling sprints were modified by not only afferent feedback from peripheral organs but also information (i.e., frequency of movement) involving subsequent exercise (8).…”
Section: Introductionmentioning
confidence: 99%